CHANGES IN MOTOR-COGNITIVE PERFORMANCES DURING AN EXERGAME INTERVENTION IN PERSONS WITH DEMENTIA. (11th November 2018) - Hauer, K; Werner, C; Wiloth, S; Lemke, N; Rosner, R
Abstract: Exergaming can be effective to improve physical and cognitive functions, motor-cognitive per-formances, and psychological outcomes in older persons with or without cognitive impairment. However, little is known about the training volume required to achieve positive effects. The aim of this study was to evaluate the time course of improvements in motor-cognitive game performances during an exergame intervention in Persons with Dementia (PwD). Fifty-six PwD (mean age = 82.7 ± 6.2, MMSE = 22.2 ± 2.8) took part in a 10-week task-specific training program (2/week = 20 sessions) on an interactive, exergame-based balance training system (Physiomat®), combining postural control tasks with cognitive tasks of an established neuropsychological test (modified Trail-Making-Test). Physiomat® performance was assessed at baseline (T1), after training session 7 (TS7) and 14 (TS14), and at post-intervention after 20 training sessions (T2) as the time required to complete different Physiomat®-Trail-Making-Tasks (PTMT). Significant improvements with large effect sizes in all PTMT were observed from T1 to TS7 (p ≤ 0.001–0.003; Cohen's d = 0.80–1.40 for effect sizes). Physiomat® performance in most PTMT did not significantly improve from TS7 to TS14, nor from TS14 to T2. Across all PTMT, significant improvements with moderate-to-large effect sizes (p ≤ 0.001–0.036; Cohen's d = 0.43–1.07) were found from TS7 to T2. Results suggest that large task-specific improvements in complex motor-cognitive performances can be achieved in PwD within a surprisingly short exergame intervention. For further increase of the performance level, a higher training volume may to be necessary to fully exploit rehabilitation potential in this vulnerable population.